2017
DOI: 10.1007/s00702-017-1771-2
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate via NMDA, AMPA/kainate, GABAA and Alpha2 receptors and by modulation of CREB/BDNF and Akt/GSK3 signaling pathway exerts neuroprotective effects against methylphenidate-induced neurotoxicity in rats

Abstract: Chronic abuse of methylphenidate (MPH) often causes neuronal cell death. Topiramate (TPM) carries neuroprotective effects, but its exact mechanism of action remains unclear. In the present study, the role of various doses of TPM and its possible mechanisms, receptors and signaling pathways involved against MPH-induced hippocampal neurodegeneration were evaluated in vivo. Thus, domoic acid (DOM) was used as AMPA/kainate receptor agonist, bicuculline (BIC) as GABA receptor antagonist, ketamine (KET) as NMDA rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…Studies have shown that activated CREB or P-CREB involvement in a variety of functional responses associated with nervous system. [40] Previous reports have confirmed that CREBdependent BDNF expression has a major role in neuronal development, neurogenesis and mood disorders such as anxiety and depression. [41] In this study, PTX had downregulated CREB, p-CREB and BDNF expressions significantly when compared to the control animals (P < 0.05).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies have shown that activated CREB or P-CREB involvement in a variety of functional responses associated with nervous system. [40] Previous reports have confirmed that CREBdependent BDNF expression has a major role in neuronal development, neurogenesis and mood disorders such as anxiety and depression. [41] In this study, PTX had downregulated CREB, p-CREB and BDNF expressions significantly when compared to the control animals (P < 0.05).…”
Section: Discussionmentioning
confidence: 93%
“…Based on these observations, it can be assumed that TCHE ameliorated PTX‐induced anxiety through modulating serotonergic, dopaminergic and noradrenergic systems. Studies have shown that activated CREB or P‐CREB involvement in a variety of functional responses associated with nervous system . Previous reports have confirmed that CREB‐dependent BDNF expression has a major role in neuronal development, neurogenesis and mood disorders such as anxiety and depression .…”
Section: Discussionmentioning
confidence: 97%
“…Recommendations may include drugs that also block calcium channels in neurons and thus, inhibit presynaptic liberation of excitatory neurotransmitters in neurons (PGB) [29]. Besides, favorable combinations of AEDs were reported for the drugs exerting several molecular mechanisms of action (i.e., with multi-targets of their anticonvulsant activity-TPM) [43][44][45]. From a theoretical point of view, the most recommended combinations should consist of PB or one of the GABA A -receptor activating drugs, LTG or OXC -or one of the sodium channel blockers, which inhibits seizure propagation in the brain and one of the multi-targets drugs like TPM, with various molecular mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the absorbance was read at 532 nm, and the results obtained were expressed as nmol/mg of protein. [3282935363738]…”
Section: Methodsmentioning
confidence: 99%
“…[12] Glycogen synthase kinase-3-beta (GSK3β) is an important intracellular regulatory protein that is subject to phosphorylation by growth factor-stimulated signaling pathways (such as BDNF). [34] GSK3β is inhibited upon serine 9-phosphorylation by growth factor receptor-induced activation of Akt. [5] GSK3β is a protein kinase that has important regulatory effects in neural plasticity and survival.…”
Section: Introductionmentioning
confidence: 99%